2015
DOI: 10.1371/journal.pone.0136769
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Catecholaminergic Phenotype in Human SH-SY5Y and BE(2)-M17 Neuroblastoma Cell Lines upon Differentiation

Abstract: Human cell lines are often used to investigate cellular pathways relevant for physiological or pathological processes or to evaluate cell toxicity or protection induced by different compounds, including potential drugs. In this study, we analyzed and compared the differentiating activities of three agents (retinoic acid, staurosporine and 12-O-tetradecanoylphorbol-13-acetate) on the human neuroblastoma SH-SY5Y and BE(2)-M17 cell lines; the first cell line is largely used in the field of neuroscience, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 29 publications
12
63
0
Order By: Relevance
“…On the other hand, many lines of evidence showed that RA-differentiated cells increase their expression of these dopaminergic markers, such as TH and DAT (Påhlman et al 1984;Lopes et al 2010;Filograna et al 2015). These discrepancies in the literature might be attributable to the varying differentiation protocols used, since there are differences between them, such as duration, cell 20 densities, serum concentration and differentiation agent (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, many lines of evidence showed that RA-differentiated cells increase their expression of these dopaminergic markers, such as TH and DAT (Påhlman et al 1984;Lopes et al 2010;Filograna et al 2015). These discrepancies in the literature might be attributable to the varying differentiation protocols used, since there are differences between them, such as duration, cell 20 densities, serum concentration and differentiation agent (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies in the literature might be attributable to the varying differentiation protocols used, since there are differences between them, such as duration, cell 20 densities, serum concentration and differentiation agent (e.g. RA, staurosporine, BDNF) (Cheung et al 2009;Agholme et al 2010;Lopes et al 2010;Filograna et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Despite all of these works, no link between oxidative stress and AChE has been identified in human brain cells. In this context, it would be interesting to know the effect of ROS on cholinergic system markers from undifferentiated SH-SY5Y neuroblastoma cells; because, although these cells are not specifically cholinergic, they present AChE enzyme as has been previously demonstrated by Filograna et al [19]. Although there are some studies about the action of pro-oxidant substances on AChE of different cell lines, to the best of our knowledge the direct effect of oxidative stress on the levels of AChE and AChE activity in human brain cells remains unclear.…”
Section: Introductionmentioning
confidence: 91%
“…Intriguingly, staurosporine, a broad-spectrum kinase inhibitor, has been used in some PD-related publications to induce cell death [6472], while other publications have used it to induce DAergic differentiation and study PD-related features [43, 44]. Early studies on SH-SY5Y cells showed differentiation towards a neuronal phenotype upon treatment with staurosporine [73, 74], which later has been characterized as catecholaminergic-like [75]. Therefore, the effects of different concentrations of staurosporine on SH-SY5Y cells should be characterized carefully to properly interpret studies that used this drug either as a differentiation agent or as an inducer of apoptosis.…”
Section: Main Textmentioning
confidence: 99%